A facile approach for preparation of polystyrene/graphene nanocomposites with ultra-low percolation threshold through an electrostatic assembly process. (6th October 2016) - Tu, Zhaokang; Wang, Jiang; Yu, Changjiang; Xiao, Hanwen; Jiang, Tao; Yang, Yingkui; Shi, Dean; Mai, Yiu-Wing; Li, Robert K.Y.
Abstract: Improving the dispersion of graphene nanosheets (GN) in a polymer matrix is a critical step in lowering the percolation threshold of nanocomposites. In this paper, an effective method based on an electrostatic assembly process is reported. Polystyrene (PS) latex was first prepared by using hexadecyl trimethyl ammonium bromide (CTAB) as a cationic surfactant, which created positive charges on the surface of the PS micelles. An in situ demulsification process was then conducted by adding negatively charged graphene oxide (GO) particles into the positively charged PS latex. Thus, GO sheets were attached spontaneously to the surfaces of PS particles through electrostatic adsorption. Followed by in situ reduction and hot pressing, the agglomeration of GN was largely prohibited by the PS microspheres and facilitated the formation of GN networks in the PS matrix. The obtained PS/GN nanocomposites exhibited excellent electrical properties with a percolation threshold as low as 0.054 vol.% GN. When the GN content reached 1.53 vol.%, the electrical conductivity was 46.32 S/m and the thermal conductivity 0.47 W/mk. This strategy represents a new environment-friendly pathway, which is also applicable for other polymer matrices, for large-scale production of polymer composites with fully interconnected graphene networks at ultra-low GN content.